Impact of Occupational Therapy on Fine Motor Skills Development of Cerebral Palsy Children - Jhalak Hasija; Sangeeta Kakkar; Ashu Kumari (International Journal of Evidence Based Nursing And Practices, 2024)
Background: Deficits in fine motor skills typically co-occur with cerebral palsy (CP), a neurological disorder that affects movement and posture. Occupational therapy is crucial for treating cerebral palsy in children and improving their capacity for independent living. This thorough summary identifies areas that require more research and highlights the most recent advancements in cerebral palsy. Aim: The purpose of this review is to investigate the effects of occupational therapy treatments on the development of fine motor skills in children who have cerebral palsy. Methodology: Numerous research on occupational therapy interventions for children with cerebral palsy were examined as part of an extensive assessment of the literature. The review concentrated on several intervention strategies: task-specific training, constraint-induced movement therapy, and sensory integration. Analysis was also done on variables affecting the results of the intervention, including the child's age, the severity of their CP, and the length of their therapy. Results: The analysis revealed that treatments for occupational therapy considerably enhance children with cerebral palsy's fine motor abilities. Task-specific training, constraint-induced movement therapy, and sensory integration all showed promising results. The child's age, the severity of their cerebral palsy, and the length of their therapy all affected how beneficial these therapies were. Conclusion: Interventions in occupational therapy can help children with cerebral palsy develop their fine motor abilities. The child's age, the severity of the ailment, and the length of therapy all impact the intervention's choice and efficacy. Implications: The results offer insightful information on occupational therapy best practices, indicating that customized therapies considering unique patient characteristics can maximize the improvement of fine motor abilities in kids with cerebral palsy. To optimize therapy outcomes, therapists can use these insights to help them choose and tailor therapies.
Keywords: Cerebral palsy (CP); Fine motor skills; Intervention strategies; Task-specific training; occupational therapy